Clinical response in dogs with acute hemorrhagic diarrhea syndrome following randomized probiotic treatment or fecal microbiota transplant - Jugan, Maria C.; KuKanich, Kate; Freilich, Leah (Frontiers in Veterinary Science, 2023)
Probiotics and fecal microbiota transplants (FMT) are two microbiome-targeted therapies that have been investigated for use in gastrointestinal diseases associated with dysbiosis. The aim of this study was to compare effects of an oral multi-strain probiotic and enema-administered fFMT on clinical signs and serum lipopolysaccharide in dogs with acute hemorrhagic diarrhea syndrome (AHDS). 18 client-owned dogs with a diagnosis of AHDS were enrolled into a randomized, blinded study at the time of hospital admission. Dogs were randomized into 2 groups: the probiotic group received a daily oral probiotic (200 x 109 CFU/10kg q 24 h) for 14 days and a single sham enema; the FMT group received a single FMT via retention enema (10 mL/kg) and placebo oral capsule for 14 days. All dogs received concurrent standard-of-care therapy, including intravenous fluids and anti-emetics; no dogs received antimicrobials. Fecal score, disease severity scores, and serum lipopolysaccharide were measured on days 0, 3, and 14. Fourteen of eighteen enrolled dogs completed the study (n = 9 probiotic; n = 5 FMT). Lipopolysaccharide decreased on days 3 and 14 from baseline and correlated with fecal score and disease severity scores. There was no difference in duration or severity of clinical signs in dogs with AHDS following an enema-administered FMT compared to probiotic treatment. Further evaluation of serum lipopolysaccharide as a marker of disease severity and recovery is warranted.